Cultura ambiental y material didáctico en alumnos de formación inicial jardín Los Arbolitos, distrito de Iquitos 2021 - Lugo Piravan, Luis Ovelio (2024)
Environmental culture plays a very important role in society because, through the materials or resources employed, it will always serve as a driving force for learning in environmental issues. This research aims to determine the correlation between environmental culture and didactic material, while also evaluating the level of environmental culture and the quality of didactic material. The population under consideration consists of students from 'Los Arbolitos' kindergarten, with a sample of 133 boys and girls. The methodology used is correlational and descriptive, taking into account school level, gender, and ages for comparison. The results of this research show a moderate correlation of 44.8% between environmental culture and didactic material. However, a very low correlation was found between these two variables and age and gender. In conclusion, environmental culture depends moderately on the didactic material used, whereas these two variables, age, and gender do not have a direct or inverse dependence.